Revealing Effective Strategies for Arabic Language Learning Implementation - Anwar , Najih; rakhmaniah, nur azizahtur (Indonesian Journal of Islamic Studies, 2024)
This study investigates the implementation of Ta'alam al-'Arabiyyah Ma'ana volume 1 in Arabic language learning at Madrasatul Alsun Sidoarjo. Employing a descriptive qualitative approach, data were gathered through observation, interviews, and documentation. The analysis reveals three stages of implementation: lesson planning, learning execution, and evaluation. Factors facilitating implementation include competent teachers, discipline, and adequate resources, while barriers include student distractions and environmental noise. Solutions proposed to address these barriers include verbal cues to refocus students and environmental adjustments. This research contributes insights for educators and policymakers to enhance Arabic language learning experiences in similar educational settings. Highligh: Detailed analysis of implementation stages. Identification of facilitating and inhibiting factors. Practical solutions to overcome implementation challenges. Keywoard: Arabic language learning, Ta'alam al-'Arabiyyah Ma'ana, Madrasatul Alsun Sidoarjo, Implementation, Qualitative research